Analysis of the influence of a cold leveling process on the properties of multi-layered aluminum sheets - Zettl, Bastian; Merklein, Marion (XLI. Verformungskundliches Kolloquium, 2023)
One approach for reducing emissions in the transportation and traffic sector is offered by lightweight material construction. In the automotive and aircraft industry, materials with a high specific strength are used, such as aluminum alloys of the 5xxx, 6xxx and 7xxx series. The strength of these alloys can be further increased by mechanical forming processes and the associated work hardening. The mechanical process group includes the so-called severe plastic deformation processes, which, by introducing very high degrees of plastic deformation, also induce the mechanism of fine-grain hardening in addition to work hardening. Accumulative roll bonding (ARB) is a process variant in which large-area semi-finished sheet products with a multilayered structure can be produced. It has already been identified that the layer interfaces and the intermediate bond strengths have a significant influence on the subsequent product properties, since delamination effects lead to premature material failure. For improving the dimensional accuracy and flatness of large-scaled sheets, straightening processes can be used. In this work, the influence of sheet leveling at room temperature on the feasibility and interface properties of ARB-products is investigated. In detail, the investigations include the analysis of the interface as well as the distribution of the sheet thickness as a function of the number of ARB process cycles in the initial state and after straightening at room temperature.<br
Keywords: accumulative roll bonding; cold leveling; multi-layered sheets

Evaluation of the friction and wear behavior of a-C:H coatings for lubricant-reduced sheet metal forming - Reblitz, Jonas; Zettl, Bastian; Seynstahl, Armin; Orgeldinger, Christian; Tremmel, Stephan; Merklein, Marion (Materials Research Proceedings, 2024)
Industrial companies are confronted with increasing demands for sustainability, challenges in the availability of raw materials as well as rising energy and labor costs. Thus, technological measures for improving the ecologic and economic potential of production are required. An important production stage for the manufacturing of metal-based products is sheet metal forming which consists of several production steps. Initially, the semi-finished sheets are lubricated with oil to reduce friction in the actual forming stage and afterwards they have to be cleaned. One approach for the decrease of production costs and increase of sustainability is the avoidance or reduction of oil-based lubricants and hence subsequent cleaning of the sheet metal parts. However, reducing the amount of lubrication leads to higher friction and wear. Consequently, the part quality as well as tool lifetime are significantly decreased. To meet these challenges, surface modifications for the reduction of wear can be applied. In this study, diamond like carbon (DLC) tool coatings were combined with minimum quantities of a solid lubricant on semi-finished parts to analyze the potential of the coatings for beneficial friction conditions. In this context, suitable a-C:H coating systems were needed to be identified. The associated friction and wear behavior was evaluated as a function of the lubricant amount for different variants of semifinished parts. Initially, several a-C:H coatings were generated with varying deposition parameters. Promising variants regarding layer adhesion were analyzed for sheet metal forming in terms of tribological behavior. The resulting coefficients of friction (CoF) and wear resistance were investigated with strip drawing tests. For the comparison of the results over different industrially relevant sheet metals, two aluminum alloys as well as one steel material with different zinc coatings were evaluated. For all materials, the amount of solid lubricant was varied in a range below 0.8 g/m2 up to a completely dry condition without lubrication. Introduction
CRIS-Team Scopus Importer:2024-11-08
Keywords: DLC Coatings; Physical Vapor Deposition (PVD); Sheet Metal; Tribology

Improvement of process control in sheet metal forming by considering the gradual properties of the initial sheet metal - Zettl, Bastian; Schmid, Harald; Pulvermacher, Samuel; Dyck, Alexander; Böhlke, Thomas; Gibmeier, Jens; Merklein, Marion (SAGE Open, 2023)
In scientific studies, sheet metal is usually considered as a two-dimensional body. Thus, it is accepted that material properties are in most cases regarded homogeneous in thickness direction. However, a gradation of certain properties becomes apparent when going beyond the standard characterization methods for sheet metals, which can for example, influence the springback behavior and the thinning of the sheet after forming. Thus, the aim of this work is to further improve the prediction accuracy of springback after forming in simulations, by implementing several inhomogeneous properties over the sheet thickness in an existing material model. For this purpose, the entire procedure from the identification of the inhomogeneous properties for describing the gradation to the implementation in a numerical model and its validation by comparing experimental and simulated bending operations is carried out on a DC04 cold-forming steel in order to prove its influence on the springback behavior. It is shown that including graded material properties in simulations does indeed have an impact on the prediction quality of springback and that the information about inhomogeneous properties can be provided by existing characterization methods with a high local resolution like electron backscatter diffraction or X-ray stress analysis. In a further step, it was possible to validate the improvement in numerical accuracy by comparing the prediction of the springback angle from both the existing and the extended model with experimental bending results. Both the initial model as well as the model supplemented with the 3D properties provide a good prediction accuracy in the solution heat treated material state. For the predeformed material, however, the initial numerical model predicts a springback angle of about 13°, which deviates remarkably from the experimentally obtained mean value of about 17°. The extended model delivers a significantly improved accuracy in springback prediction in relation to the initial prediction (deviation of 4°) with a minor deviation of only about 0.8°, which proves the importance of considering the gradation of material properties in thickness direction for an overall higher dimensional accuracy of sheet metal product
Keywords: sheet metal; forming; springback; simulation; microstructural modelling; strain; residual stress; characterization

Investigation of a novel automated surface treatment method within accumulative roll bonding of AA6016 sheets - Zettl, Bastian; Merklein, Marion (Journal of Manufacturing Processes, 2025)
In order to minimize resource utilization and fuel consumption in the transportation and construction sector, possibilities to further enhance the mechanical properties of structural metal alloys are very lucrative. Especially in times of increasing energy costs as well as prices for certain elements, conventional heat treatments as well as alloying routes can be problematic. In this context, purely mechanical methods are capable of providing significant strengthening of already established alloys. Belonging to these methods and especially suitable for sheet metals, is the so-called Accumulative Roll Bonding (ARB) process. It enables the cumulation of the forming degree within the material and can lead to the evolution of an ultrafine grain sized microstructure. However, it severely lacks in its reproducibility and efficiency due to many influencing factors in the process chain. For this, the introduced work focuses on the least investigated step in the process chain, the surface treatment. For this, a novel and automated brushing method is analyzed in terms of its reproducibility as well as feasibility within ARB. Through roughness and topography measurements, it is shown that the force as well as the dwell time of the active brushing contact has a high influence on the resulting surface condition. Additionally, the run-in behavior and the deflection of the brush must be taken into account in order to generate a homogeneous surface finish. By selecting a suitable combination of parameters within the novel surface treatment method, a significant improvement regarding the scattering of the bonding strength is proven. Whereas the conventional manual surface treatment leads to fluctuations of the bonding strength of around 35 %, the newly introduced method displays a clearly reduced deviation of only 1.6 %. This enables to derivate cause-effect relationships between the input parameters regarding brushing, the resulting surface condition and the resulting bonding properties of ARB sheets.
CRIS-Team Scopus Importer:2025-04-11
Keywords: Accumulative roll bonding; Aluminum; Automation; Surface treatment

Investigation of the direct recyclability of chip waste by cold cup extrusion and identification of its potential in continuous processes - Zettl, Bastian; Kraus, Martin; Böhm, Wolfgang; Zippert, Patrick; Merklein, Marion (Forming Technology Forum 2022, 2022)
Environmental protection and the responsible use of natural resources are currently the main challenges facing our society. When machining metallic materials, the formation of chips is unavoidable caused by technological reasons. This leads to a large proportion of chip waste. This waste needs to be subsequently recycled in energy-intensive cleaning and melting processes. To face these, this work is dealing with a novel direct recyclability method of chips from technically pure aluminum EN AW-1050A and pure copper CW004A by cold cup extrusion. The cups are characterized in regard to their bonding quality by light microscopy and X-ray analysis in order to prove the feasibility of the method. The objective is to demonstrate the suitability of cold cup drawing for creating cohesive bonds even under varying chip properties. Additionally, the usage of chip waste for recycling without melting in a continuous forming process is analyzed. For this, the so called Temconex® method is introduced, which enables the production of semi-finished profiles by a combination of friction and severe plastic deformation in an extrusion process.<br
Keywords: recycling; chips; cyclic economy; extrusion; sustainability; aluminum; copper

Investigation of the joinability of single- and multi-layered AA6014 sheets produced by accumulative roll bonding in the shear-clinching process - Zettl, Bastian; Wiesenmayer, Sebastian; Kraus, Martin; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers Part L-Journal of Materials-Design and Applications, 2022)
Accumulative roll bonding belongs to the severe plastic deformation processes and is suitable for producing multi-layered as well as high-strength sheets through repeated rolling. After four accumulative roll bonding-cycles, the strength of the investigated AA6014-T4 alloy is elevated due to strain and fine grain hardening by 170% in yield strength and by 37% in ultimate tensile strength. This is accompanied by a significant decrease in material ductility which is disadvantageous for joining processes based on forming operations. Shear-clinching, however, can be used to join high-strength and low-ductile materials on the die side. Thus, it is a promising method for the mechanical joining of accumulative roll bonding components. The multi-layered and more brittle material is located on the die side whereas the single-layered base material with higher ductility is positioned on the punch side. At present, there is no scientific knowledge how the multi-layered material behaves in the shear-clinching process. Since the material is cut in the process, delamination effects could occur at the interfaces produced via accumulative roll bonding. Additionally, the investigation aims at the influence of the accumulative roll bonding process on the properties of the joints. They are expected to depend on the number of process cycles and thus on the change of mechanical properties of the multi-layered material. The bond strength of the shear-clinched joints is determined by shear and tensile tests. The areas of material failure are analysed via metallographic methods. From the failure behaviour and load-bearing capacity it is determined which number of accumulative roll bonding cycles is ideal for joining multi-layered sheets via shear-clinching.
CRIS-Team Scopus Importer:2022-02-04
Keywords: accumulative roll bonding; Joining; multi-layered materials; shear-clinching

Investigation of the tensile response and the microstructural evolution during hot drawing of multi-layered, ultrafine-grained AA6014 sheets by thermomechanical analyzes - Zettl, Bastian; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2022)
Mechanical strengthening of sheet material can be realized by accumulative roll bonding, which belongs to the severe plastic deformation processes. Beside fine-grain hardening also work and precipitation hardening is responsible for the rise of material strength. However, this is also accompanied by a significant decrease in ductility. Thus, the need for an enhancement of ductility is essential for a sufficient formability in later applications and was already introduced by tailored heat treatments. The challenge, however, is to realize a process temperature that leads to a degradation of dislocations and dissolution of MgSi-precipitations, without a recrystallization of the fine-grained microstructure to coarse grain sizes. In order to identify a suitable temperature range to avoid recrystallization, hot forming experiments are carried out at successive temperatures from 20 to 300 °C. Tensile specimens are drawn with the thermomechanical simulator Gleeble 3500 (Dynamic Systems Inc.) aided by the strain measurement system Aramis (GOM GmbH). The aim is to investigate the dependence of the mechanical properties from the forming temperature in order to identify a temperature range, in which high strength with simultaneous enhanced ductility is maintaine

Robot-assisted surface treatment strategies of AA6014 sheet metal for accumulative roll bonding - Zettl, Bastian; Merklein, Marion (ESAFORM 2021 - 24th International Conference on Material Forming, 2021)
The application of high strength aluminum sheet metal components in automotive and aviation products effectively saves material and thus weight. Material strengthening can be realized by accumulative roll bonding (ARB), which belongs to the severe plastic deformation processes. Through repeated rolling steps a multilayered sheet metal is produced, which possesses increased strength due to its ultra-fine grained microstructure. Prior to each rolling step a surface treatment via wire brushing is mandatory for removing the oxide layer and roughening the sheet surface, which enables the bonding between the unique layers during rolling. The necessary surface treatment of the sheets is not fully understood by the current state of the art. In the past, it was not possible to achieve a defined and stable surface finish, because the brushing operation was done manually. The improvement of the process stability is essential to determine the relationship between the input parameters for brushing and the resulting bond strength of multilayered ARB sheets. For this reason, a robot-controlled surface treatment is introduced. The investigated material is the precipitation-hardened aluminum AA6014 with a sheet thickness of 1 mm. A suitable brushing kinematic under constant load is implemented and its effects on the surface properties are investigated by roughness measurements. The investigation shows, that the parameter combination leads to comparable or even higher roughness values than through manual brushing. Through 16 consecutive brushing paths a homogeneous and sufficient high surface roughness is realized, which enables material bonding in the rolling step. Thus, the research results indicate, that the robot-assisted surface treatment of ARB sheet metal is a promising method for a better automation and reproducibility of the brushing and the overall ARB process.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Accumulative roll bonding; Robot-assisted brushing; Roughness; Surface treatment